Short-term survival in extensive craniofacial resections (Clinics, 2021)
OBJECTIVES: Craniofacial resection (CFR) procedures for craniofacial tumors with cranial extension are often extensive. Although CFRs may yield good oncological results, there are concerns about high perioperative morbidity and mortality. This study aimed to determine risk factors for perioperative mortality after open CFR in terms of deaths occurring during index hospitalizations. METHODS: We conducted a retrospective analysis of CFRs conducted at a tertiary oncology hospital from May 2009 through December 2018. RESULTS: Our analysis included data from the medical records of 102 patients, the majority of whom were male (n=74, 72.5%). The mean age was 61 years (±18.3 years). Skin malignancies (n=64, 63.4%) accounted for nearly two-thirds of the treated tumors, and most of these were squamous cell carcinoma. Postoperative medical complications occurred in 33 patients (33%), and surgical complications occurred in 48 (47%). Multivariate analysis revealed the only independent risk factors for perioperative deaths to be the presence of intracranial tumor extension on preoperative imaging (hazard ratio [HR]=4.56; 95% confidence interval [CI]: 1.74–11.97; p=0.002) and the unexpected emergence of postoperative neurological dysfunction (HR=10.9; 95% CI: 2.21– 54.3; p=0.003). CONCLUSIONS: In our study, factors related to tumor extension were associated with a higher risk of perioperative death.